Operator algebras, operator theory and applications - Bastos, Maria Amélia (Springer, 2017)
This book is composed of three survey lecture courses and nineteen invited research papers presented to WOAT 2006 - the International Summer School and Workshop on Operator Algebras, Operator Theory and Applications, which was held at Lisbon in September 2006. The volume reflects recent developments in the area of operator algebras and their interaction with research fields in complex analysis and operator theory. The lecture courses are: Subalgebras of Graph C*-algebras, by Stephen Power: An introduction to two classes of non-selfadjoint operator algebras, the generalized analytic Toeplitz algebras associated with the Fock space of a graph and subalgebras of graph C*-algebras; C*-algebras and asymptotic spectral theory, by Bernd Silbermann: Three topics on numerical functional analysis that are the cornerstones in asymptotic spectral theory: stability, fractality and Fredholmness; Toeplitz operator algebras and complex analysis, by Harald Upmeier: A survey concerning Hilbert spaces of holomorphic functions on Hermitian symmetric domains of arbitrary rank and dimension, in relation to operator theory, harmonic analysis and quantization